Time-frequency analysis of red-green visual flickers based on steady-state visual evoked potential recording - Dechwechprasit, Panisa; Phothisonothai, Montri; Tantisatirapong, Suchada (My University, 2017)
The study of brain activity can be done by visual stimulus flickering at specific frequencies, Steady-State Visual Evoked Potential or as known as SSVEP. SSVEP is to stimulate the EEG signal to locate the desired goal of the experiment when a visual stimulus flickering with different constant frequencies and same duration. We aim to present a case study of electroencephalogram (EEG) signal by analyzing the frequency response of the red and green light. The stimulation is based on SSVEP by dividing the trial into two trials: single light and two lights. We considered three parameters that are light color, frequency and epoch interval. The optimal experimental results showed the classification accuracy rate of 74% and 75% for single and two color lights, respectively. The results can be considerably applied to the brain-computer interface (BCI) system.
Keywords: Brain-Computer Interface (BCI); Electroencephalogram (EEG; Steady State Visually Evoked Potential (SSVEP)